Does carbon monoxide treatment alter cytokine levels after endotoxin infusion in pigs? A randomized controlled study - Winsö Ola; Haney Michael; Johansson Göran; Abrahamsson Pernilla; Åberg Anna-Maja; Larsson Jan (BMC, 2008)
Abstract Background Carbon monoxide (CO) has recently been suggested to have anti-inflammatory properties, but data seem to be contradictory and species-specific. Thus, in studies on macrophages and mice, pretreatment with CO attenuated the inflammatory response after endotoxin exposure. On the other hand, human studies showed no effect of CO on the inflammatory response. Anti-inflammatory efficacy of CO has been shown at concentrations above 10% carboxyhaemoglobin. This study was undertaken to elucidate the possible anti-inflammatory effects of CO at lower CO concentrations. Methods Effects of CO administration on cytokine (TNF-alpha, IL-6, IL-1beta and IL-10) release were investigated in a porcine model in which a systemic inflammatory response syndrome was induced by endotoxin infusion. Endotoxin was infused in 20 anaesthetized and normoventilated pigs. Ten animals were targeted with inhaled CO to maintain 5% COHb, and 10 animals were controls. Results In the control group, mean pulmonary artery pressure increased from a baseline value of 17 mmHg (mean, n = 10) to 42 mmHg (mean, n = 10) following 1 hour of endotoxin infusion. Similar mean pulmonary artery pressure values were found in animals exposed to carbon monoxide. Plasma levels of all of the measured cytokines increased in response to the endotoxin infusion. The largest increase was observed in TNF-alpha, which peaked after 1.5 hours at 9398 pg/ml in the control group and at 13395 pg/ml in the carbon monoxide-exposed group. A similar peak was found for IL-10 while the IL-6 concentration was maximal after 2.5 hours. IL-1beta concentrations increased continuously during the experiment. There were no significant differences between carbon monoxide-exposed animals and controls in any of the measured cytokines. Conclusion Our conclusion is that 5% COHb does not modify the cytokine response following endotoxin infusion in pigs.